A Novel Tea factory waste metal-free catalyst as promising supercapacitor electrode for hydrogen production and energy storage: A dual functional material. (1st December 2021) - Özarslan, Saliha; Raşit Atelge, M.; Kaya, Mustafa; Ünalan, Sebahattin
Highlights: The material is defined as dual functional, named as 'cap-cat' by us. Hydrogen production rate was found as 23, 507 mLmin -1 gcat −1 for 60 °C. The activation energy of the catalyst was determined to be 38.6 kJ mol −1. The electrode material was found to be 155F/g at the current density of 2A/g. Abstract: In this study, the catalyst produced from tea factory waste (TFW) was used for the first time for hydrogen production by methanolysis of sodium borohydride (NaBH4 ). The produced material had a dual function as both catalyst and supercapacitor; therefore, it was named 'cap-cat'(capacitor-catalyst) by us. In this context, TFW was treated with acetic acid for 24 h at 80 °C. The sample was then subjected to combustion in the oven to synthesize the catalyst. Afterward, the most efficient TFW-CH3 COOH catalyst was synthesized by evaluating different acid ratios, burning temperatures and times. The best conditions for the acetic acid ratio, burning temperature, and time were found out 3 M, 300 °C, and 60 min. The characterization of the catalyst was done using SEM-EDX, FTIR, XRD analysis. Hydrogen generation experiments from NaBH4 by methanolysis were performed at various catalyst concentrations in the range of 0.05–0.2 g, diverse NaBH4 ratio of 1 to 7.5%, and at different reaction temperatures (30–60 °C). The HGR of the synthesized catalyst was recorded as 3096.4, 8367.5, 11227.9, and 23, 507 mLmin -1 gcat -1 for these temperatures (30, 40, 50, and 60 °C), respectively. Also the activation energy was calculated as 38.6 kJ mol −1 . Subsequently, the CV (cyclic voltammetry) and charge–discharge curves of the prototypes produced were substantially similar to the supercapacitor curves in the literature. Gravimetric capacitance was found to be 155F/g at a current density of 2 A/g.